Uncertainties in Shoreline Projections to 2100 at Truc Vert Beach (France): Role of Sea‐Level Rise and Equilibrium Model Assumptions. Issue 8 (5th August 2021) - D'Anna, M.; Castelle, B.; Idier, D.; Rohmer, J.; Le Cozannet, G.; Thieblemont, R.; Bricheno, L.
Abstract: Sandy shorelines morphodynamics responds to a myriad of processes interacting at different spatial and temporal scales, making shoreline predictions challenging. Shoreline modeling inherits uncertainties from the primary driver boundary conditions (e.g., sea‐level rise and wave forcing) as well as uncertainties related to model assumptions and/or misspecifications of the physics. This study presents an analysis of the uncertainties associated with future shoreline evolution at the cross‐shore transport dominated sandy beach of Truc Vert (France) over the 21st century. We explicitly resolve wave‐driven shoreline change using two different equilibrium modeling approaches to provide new insight into the contributions of sea‐level rise, and free model parameters uncertainties on future shoreline change in the frame of climate change. Based on a Global Sensitivity Analysis, shoreline response during the first half of the century is found to be mainly sensitive to the equilibrium model parameters, with the influence of sea‐level rise emerging in the second half of the century (∼2050 or later), under several simulated scenarios. The results reveal that the seasonal and interannual variability of the predicted shoreline position is sensitive to the choice of the wave‐driven equilibrium‐based model. Finally, we discuss the importance of the chronology of wave events in future shoreline change, calling for more continuous wave projection time series to further address uncertainties in future wave conditions. Our contribution demonstrates that unmitigated climate change can result in shoreline retreat of several tens of meters by 2100, even for sectors that have been stable or slightly accreting over the last century. Key Points: Ensemble‐based simulations of future shoreline evolution to 2100, including sea‐level rise driven erosion, are performed and analyzed Future shoreline projections uncertainties are initially controlled by modeling assumptions and after 2060 by sea‐level rise uncertainties The choice of wave‐driven equilibrium modeling approach and incident wave chronology are critical to short/mid‐term shoreline projections